2017
DOI: 10.1038/tpj.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib-induced ophthalmological side-effects in GIST patients are associated with the variations of EGFR, SLC22A1, SLC22A5 and ABCB1

Abstract: Imatinib-induced ophthalmological side-effects, including conjunctiva hemorrhage and periorbital oedema, although very common and still remain relatively little understood. The present study investigated the effects of genetic polymorphisms of drug targets and membrane transporters on these side effects. We found that the minor allele of EGFR rs10258429 and SLC22A1 rs683369 were significant risk determinants of conjunctival hemorrhage with OR of 7.061 (95%CI = 1.791-27.837, P = 0.005 for EGFR rs10258429 CT +TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
3
18
1
Order By: Relevance
“…Imatinib mesylate is a TKI that inhibits the BCR-ABL, c-Kit and PDGFR tyrosine kinases. 2 Imatinib is mainly used in the treatment of chronic myeloid leukaemia (CML) and GISTs. In addition to cancer cells, the tyrosine kinase enzymes of non-cancer cells also get inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib mesylate is a TKI that inhibits the BCR-ABL, c-Kit and PDGFR tyrosine kinases. 2 Imatinib is mainly used in the treatment of chronic myeloid leukaemia (CML) and GISTs. In addition to cancer cells, the tyrosine kinase enzymes of non-cancer cells also get inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…OCT1 is primarily expressed in hepatocytes and the hepatic excretion of drugs will be influenced by the lower functioning haplotypes. Qiu et al and Singh et al showed that rs6383369 (F160L) and rs628031 (M480V) reduced the clearance of imatinib [49,52]. In OCT1, the loss-of-function genetic variants showed lower uptake activity in all reported polymorphisms for metformin and imatinib, and also showed a decreased clearance of morphine.…”
Section: Genetic Polymorphisms In the Oct1 Gene (Slc22a1)mentioning
confidence: 99%
“…Case-control study demonstrated that G risks allele at SNP rs27437 in SLC22A5 gene was associated with colorectal cancer risk (69). Study on GIST patients suggested that investigation on minor allele of SLC22A5 may assist to optimise imatinib therapy (70,71).…”
Section: Slc22a5mentioning
confidence: 99%